The effect of neighborhood walkability on changes in physical activity and sedentary behavior during a 12-week pedometer-facilitated intervention. - Gavin R McCormack; John C Spence; Tara-Leigh McHugh; W Kerry Mummery (PLoS ONE, 2022)
Background Pedometer-facilitated interventions encourage physical activity via the accumulation of steps. Mixed evidence suggests that neighborhood walkability might influence the effectiveness of physical activity interventions, including pedometer-facilitated interventions. Our study investigated the moderating effect of neighborhood walkability on immediate (4-week) and short-term (12-week) changes in self-reported neighborhood-specific leisure and transportation walking, leisure-based moderate and vigorous-intensity physical activity, and leisure-based screen time during a pedometer-facilitated intervention (UWALK). Methods This quasi-experiment undertaken in Calgary (Canada) compared behavior changes during the 12-week intervention between two neighborhood groups classified as 'walkable' or 'car dependent' based on Walk Score®. Of the 573 volunteers (adults in the contemplation and preparation stages of physical activity behavior change), 466 participated in UWALK. Surveys captured sociodemographic characteristics, perceived neighborhood walkability, neighborhood preferences, motivation, physical activity and screen-based leisure. Covariate-adjusted linear mixed models estimated the differences in physical activity and leisure screen time between the neighborhood walkability groups at baseline, 4-weeks, and 12-weeks. Results UWALK participants included mostly females (83%) and had an average age of 49.2 years. Weekly minutes of walking for transport inside the neighborhood was higher (p < .001) among participants from walkable versus car dependent neighborhoods at baseline (42.5 vs. 21.1), 4-weeks (81.2 vs. 48.2), and 12-weeks (87.2 vs. 48.0). Regardless of neighborhood walkability, all physical activity outcomes were higher and leisure screen time lower at 4-weeks and 12-weeks compared with baseline. We found no significant neighborhood group by time interactions. Conclusions Pedometer-facilitated interventions may be effective for supporting short-term changes in physical activity and sedentary behavior even among adults residing in low walkable neighborhoods.